EFFECT OF DRUGS ON ORTHODONTIC TOOTH MOVEMENT: A REVIEW - DANALAKSHMI.J,; DR.S.P. SARAVANA DINESH, (International Journal of Pharma and Bio Sciences, 2016)
The pharmacologic agents that would be practical for orthodontic practice are much more limited than those used in other disciplines of dentistry. However thisdoesn't mean that a full understanding of the pharmacology of drug action, it's side effects, and possible contraindications are unnecessary. The objective of this review is to outline the effects and the adverse effects of various drugs on orthodontic tooth movement in patients undergoing orthodontic treatment. Remodelling of periodontal tissues facilitates orthodontic tooth movement in response to mechanical forces. To avoid undesirable influences on tooth movement Orthodontist should be aware of any drug taken by each individual patient. Some of the commonly used drugs like analgesics, NSAIDs like aspirin, COX-2 inhibitors, acetaminophen, vitamin D, prostaglandins, fluorides, relaxin, calcitonin, bisphosphonates, corticosteroids, immunosuppressant’s, anticancer drugs, antibiotics, anti-convulsants, interleukins have major influence on bone remodelling and tooth movement. Hence care has been taken in this article to review the influence of all these drugs on orthodontic tooth movement.